Analisis Sistem Pengendalian Internal Terhadap Pengelolaan Piutang Usaha Pada Yogyakarta Marriott Hotel - Franciska Rizky Alvionnita; Agus Sholikhin; I Gusti Ayu Agung (Sekolah Tinggi Pariwisata Sahid Surakarta, 2021)
This research explained about how the implementation of internal control and the effectiveness of accounts receivables internal control. This research was conducted at july 2019 till January 2020 the purpose of this is how the implementation of internal control and the effectiveness of accounts receivables internal control. In This Research, the researcher uses descriptive and kuantitatif methods,the population of this research is 10 employee Finance Department,the sample of this research is employee Finance Department who has specific criteria in this . And the tehnic of data collection observation with non participants and documents study about tourist attraction. The results of this research are how to implement the empowerment system at the Marriott Hotel Yogyakarta, including the authorization of the documents used, as well as the completion of various documents used in accounts receivable transactions. The conclusion from the business management system at the Marriott Hotel, the internal control system is quite effective. The author provides several recommendations to the Yogyakarta Marriott Hotel that the company should improve the accuracy and consistency of the work of each division by referring to the LSOP(Local Standard Operating Procedure) from Marriott International.